A social identity complexity theory reading of Philemon - Kok, Jacobus (HTS teologiese studies, 2021)
This article provides new perspectives on navigating complex social identity in the letter to Philemon by means of the heuristic use of social identity complexity theory (SICT) in combination with socio-rhetorical analysis (SRA). The application of SICT as a heuristic tool in New Testament (NT) studies is relatively new, but it is positioned within the novel research being carried out on social identity theory in the NT.Contribution: This article wants to make a new contribution by illustrating how SICT can help us to think in more nuanced ways about nested identity(s) in Philemon.